The practice of pilot/feasibility studies in informing the conduct of HIV related clinical trials in sub-Saharan Africa: A scoping review - Nalubega, Sylivia; Obado Osuwat, Lawrence; Agyeiwaa, Poku Brenda; Evans, Catrin; Matovu Junior, John Bosco (Contemporary Clinical Trials Communications, 2022)
Pilot/feasibility studies represent a fundamental phase of the research process and play a vital role in the preliminary planning of a full size HIV clinical trial. Published HIV clinical trial protocols were reviewed to establish the extent to which the proposed HIV clinical trials are informed by a prior pilot/feasibility study. Methods: The JBI methodology for scoping reviews was followed. Six databases were systematically searched to identify articles for inclusion. Results: Thirty two (32) published HIV study protocols were included. Articles were in the English language and were published in the past 10 years (2011–2020). The review results showed that the majority of HIV-related clinical trials in sub-Saharan Africa were not informed by pilot/feasibility studies. The results further indicated that the number of HIV clinical trials informed by a pilot/feasibility study have been on the increase in the 8 years’ period since 2012, a trend that indicates positive uptake of pilot studies in HIV related studies. A few select countries (South Africa, Uganda, Zimbabwe, Malawi and Kenya) comprised more than 70% of all clinical trials that were informed by a pilot/feasibility study, conducted in sub Saharan Africa. Conclusions: Although there is an increasing interest among researchers to integrate pilot/feasibility studies in HIV related research, limited countries in sub-Saharan Africa appear to have embraced this trend. Strategies that can motivate researchers to engage in a culture of incorporating pilot/feasibility studies in HIV related research should be implemented.
Keywords: Pilot studies; Feasibility studies; HIV/AIDS; Clinical trials; Sub-saharan africa; Scoping review